How housing problems affect students: analysis of in-depth interviews with Polish student occupation strike participants - Kurowska, Zuzanna; Socha, Jakub; Gabryszewska, Kinga (Society Register, 2024)
Factors such as the commodification of housing and higher education or the decreasing welfare support offered to students make housing and, thus, higher education less affordable. Growing difficulties can result in social dissatisfaction, manifested through protests calling for more excellent institutional support. Employing a case study method, we use phenomenological style in-depth individual interviews to explore housing experiences and perspectives of students, a group strongly affected by the growing housing issues. Thirty interviews were conducted with participants of a student occupation strike in Poznań (Poland) “Jowita” student dormitory in December 2023. Findings revealed that students struggle with alienation, rental power imbalance, or unmet housing needs. To finance housing during education, they have to work to sacrifice their health or growth. Findings indicate growing housing problems, students’ experiences, and various costs associated with continuing their education. Although the study was affected by the sudden nature of the interviews and the specificity of respondents, it shows the importance of exploring the students’ perspective of housing experiences to understand their needs better when discussing institutional support. This research contributes to further understanding of the student housing market, presenting various costs students face when managing their accommodation.